Enhancing E-Government Implementation Through Website Management - savandha, Septien Dwi; Azzahra, Adelia (Ridwan Institute, 2024)
This study explores the effectiveness of village website management in facilitating e-government implementation within Kebarepan Village, Plumbon District, Cirebon Regency. It assesses four key indicators of program effectiveness: program success, target success, satisfaction with the program, and levels of input and output. Employing a qualitative or naturalistic approach, data were collected through literature review and field study, incorporating observations, interviews, and documentation. Analysis indicates that village website management significantly enhances e-government implementation effectiveness, encompassing program success, target success, satisfaction with the program, and levels of input and output. However, certain obstacles hinder the complete realization of effectiveness. This study enhances comprehension of e-government implementation at the village level and provides insights into addressing existing barriers. The implications of these findings can inform policymakers and practitioners in optimizing e-government effectiveness within village settings.